A retrospective cohort analysis of alignment parameters for spinal tumor patients with instrumentation at the cervicothoracic junction - Christian B. Schroeder, ScM; Madison J. Michles, MS; Rahul A. Sastry, MD; Alexander A. Chernysh, BS; Owen P. Leary, BS; Felicia Sun, MD; Joaquin Q. Camara-Quintana, MD; Adetokunbo A. Oyelese, MD, PhD; Albert E. Telfeian, MD, PhD; Jared S. Fridley, MD; Ziya L. Gokaslan, MD; Patricia Zadnik Sullivan, MD; et al. (North American Spine Society Journal)
Background: Previous research on spinal alignment and postoperative outcomes after cervical and upper thoracic fixation has suggested that clinical and patient-reported outcomes are improved when certain anatomical parameters are maintained. These parameters include the cervical sagittal vertical axis (cSVA), C2 and T1 slopes, and cervical lordosis (CL). For patients with primary and metastatic tumors involving the subaxial cervical and/or upper thoracic spine, there is minimal guidance on how to apply these parameters. Surgeons must make critical decisions when designing the optimal construct, considering patient life expectancy, bone quality, oncology goals and deformity. This study aims to evaluate the impact of cervical spine alignment parameters on postoperative hardware failure in spine tumor patients and highlight instances of complications in patients with instrumentation crossing the cervicothoracic junction (CTJ). Methods: A retrospective review of a single institutional spine tumor database identified seventeen patients who underwent spinal fusion crossing the CTJ from 2015 to 2023. All patients had postoperative neutral standing radiographs with measurable cSVA, C2 and T1 slopes, and/or CL. The primary endpoint was instrumentation failure, defined as hardware pull out or breakage, and secondary endpoints included other complications including wound infection and spinal fluid leak. Results: The number of instrumented levels ranged from 3 to 15 segments with a mean of 7.47. Surgical approaches included anterior (n=3), posterior (n=12), and simultaneous anterior and posterior (n=2). The mean cSVA was 3.39±1.02 cm (range 1.59–4.9 cm). Fourteen patients had measurable C2 slopes with a mean of 25.03±9.16° (range 8.7 - 38.6°). Ten patients had measurable T1 slopes with a mean of 31.5±11.54° (range 18.4–59.6°). Thirteen patients had a measurable CL with a mean of 9.13±9.93° (range 0–37.5°). No cases of instrumentation failure were noted. Four patients experienced other postoperative complications (24%), but rates did not vary with increasing deviation from ideal parameters for cSVA, C2 and T1 slope, or CL. Conclusions: Although there was wide variability in alignment parameters in this cohort, there were no instances of hardware failure with crossing the CTJ at a mean follow-up of 41 months. The overall complication rate was high at 24%. Despite common concerns about the impact of exaggerated slope and SVA on instrumentation failure these results suggest that cervical and upper thoracic tumor patients may still have a satisfactory result following CTJ fixation, even with unfavorable alignment parameters. Larger prospective studies are needed.